Dietetics and morale, medicine and philosophy in Hellenistic Antiquity - Molina González, Liliana Cecilia (Estudios de Filosofía, 2010)
Understanding the moral dimension of Dietetics in antiquity requires researching the advances in medical investigation due to which the basis of Moral Psychology are established. Because of this in this article there is an exploration of some passages of On the Opinions of Hippocrates and Plato, written by the alexandrian physician Galen of Pergamus (I-II a. C). According to the findings of his research into the nature of the soul, even though it has a proper substance, foreign to the humorous mixtures of the body, one must admit that its faculties, including the rational one, can be aided or impeded by the balance or the upsetting of the humours in the body. This is the thesis he will defend in a work he wrote in his mature age, the faculties of the soul follow the temperaments of the body. For Galen, as before for Aristotle and Plato, the form on life which includes nutrition, has an effect on either health or sickness of the soul. In the tradition before him the moral dimension of Dietetics was already accepted, but our thesis is that in the researches of Galen on the physiology of the faculties of the body, we find the empirical base to state that the care of the body has an influence on the health of the soul.